Control of collateral formation as a therapeutic for cardiovascular disease - Amartey, Jason (2024)
Peripheral arterial disease (PAD) leads to tissue ischaemia due to vascular insufficiency. In response to this ischaemia, circulating monocytes produce vascular endothelial growth factor (VEGF-A), a crucial regulator of angiogenesis. Monocytes exhibit increased overexpression of the anti-angiogenic VEGF-A isoform, termed VEGF-A165b which is generated by alternative splicing of the VEGF gene. VEGF splicing is under the control of phosphorylation of serine/arginine splicing factors (SRSFs), orchestrated by splicing factor kinases like serine-arginine protein kinase 1 (SRPK1) and CDC-like kinase (CLK). While the role of these kinases has been established in other cell types, their role in monocytes remains relatively unknown.